Pediatric brain tumors: A bibliometric analysis - Özbek, Muhammet Arif; Yardibi, Fatma; Genç, Berkhan; Başak, Ahmet Tulgar; Tahta, Alican; Akalan, Nejat (Springer Science and Business Media Deutschland GmbH, 2022)
Purpose The purpose of this study was to identify tendency and current issues in research on pediatric brain tumors over the past 20 years and to help researchers and investors explore new directions for future research in this subject. Methods Web of Science Core Collection was used for article selection and CiteSpace 5.8.R 1 was used for bibliometric analyses with these articles. Results The overall h-index was found to be 131 in the analysis made in a total of 4019 publications on the subject between the years 2000 and 2021. A total of 16,101 authors have published articles on pediatric brain tumors. The most active author in this field was Michael D. Taylor (h-index: 105). The publication which received the strongest citation burst among publications was published in 2016 by Louis et al. published in Acta Neuropathologica, and its content is the World Health Organization's classification of central nervous system tumors. Considering the country contribution, the USA is seen in the leading position. The most publications on the subject were followed by the Journal of Clinical Oncology. Conclusion By examining the studies on childhood brain tumors carried out around the world, the subjects that can be determined as the focus were tried to be highlighted. And it has been seen that the scientific and industrial community should work together and the financial support for multidisciplinary studies should increase.
Keywords: Bibliometric Analysis; Citespace; Pediatric Brain Tumors; Pediatric Neurosurgery